Kepemimpinan Transformasional dalam Menghadapi Perubahan Organisasi - Arifim, Muhammad; Nugroho Edie Santoso; Harmawan Teguh Saputra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the application of transformational leadership in addressing organizational change at Baiturromah Vocational High School, specifically in the context of curriculum adjustment and educational technology adoption. The research method used was a qualitative case study approach. Data were collected through in-depth interviews, participant observation, and document analysis with the principal, teachers, and administrative staff. Data were then analyzed thematically to identify leadership patterns and strategies in the organizational transformation process. The results indicate that the principal implemented the four dimensions of transformational leadership: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. This implementation had a positive impact on increasing teacher participation, internal collaboration, strengthening partnerships with industry, and enhancing student learning motivation. Obstacles that emerged included resistance to change, limited facilities, a digital competency gap, and suboptimal internal communication. Strategies used by the principal to overcome these challenges included ongoing training, a persuasive approach, strengthened communication, and external collaboration. The conclusion of this study confirms that transformational leadership is effective in driving adaptive, collaborative, and sustainable organizational change, provided it is tailored to the context and resource readiness of the educational environment. Keywords: Transformational Leadership, Organizational Change, Vocational Education